2009
DOI: 10.1007/s11085-009-9176-8
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation of the Al3Mg2 Complex Metallic Alloy

Abstract: International audienceHigh temperature air oxidation of the Al3Mg2 complex metallic alloy was investigated on powder samples and bulk polycrystals in the temperature range 350–420 °C by thermogravimetric measurements, SEM and TEM. Oxidation at 420 °C on the polycrystalline samples comprised three successive phases characterised by linear kinetics laws. The first stage corresponded to the formation of a porous non adherent nanocrystalline MgO scale having a cauliflower morphology. A first acceleration in the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Decomposition and Oxidation of Magnesium Diboride the reactants can be very fast. 18 The succession of linear portions and sudden increase in the oxidation rate observed in our experiments indicate that the oxide layer which is formed on the surface is never protective in our oxidation conditions. It is inferred that the polycrystalline MgO and t-Mg 2 B 2 O 5 layer provide preferential diffusion paths along the oxides grain boundaries.…”
Section: February 2012mentioning
confidence: 63%
See 1 more Smart Citation
“…Decomposition and Oxidation of Magnesium Diboride the reactants can be very fast. 18 The succession of linear portions and sudden increase in the oxidation rate observed in our experiments indicate that the oxide layer which is formed on the surface is never protective in our oxidation conditions. It is inferred that the polycrystalline MgO and t-Mg 2 B 2 O 5 layer provide preferential diffusion paths along the oxides grain boundaries.…”
Section: February 2012mentioning
confidence: 63%
“…) shows that the weight gain rate is nearly to be constant for the first two oxidation stages. Linear growth rates are usually ascribed to the formation of non protective layers, in which the diffusion of the reactants can be very fast . The succession of linear portions and sudden increase in the oxidation rate observed in our experiments indicate that the oxide layer which is formed on the surface is never protective in our oxidation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [14], oxidation of an Al3Mg2 alloy was considered. The reaction was observed to proceed 2 in three stages with three distinct rates: an MgO layer was reported to form initially; then MgAl2O4 oxide was produced, which finally cracked, leading to the third oxidation stage.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the feasibility of Al-based alloys to improve combustion performance compared to pure Al powders, with the majority of studies concentrating on Al-Mg, Al-W, or Al-Li [26][27][28][29][30][31][32][33][34][35]. To obtain the ignition characteristics of alloy particles, Corcoran et al [36] studied single particles of the Al-Mg alloy (1-50 µm, Mg:10-53% mol) in high-temperature mixed acetylene/airflow.…”
Section: Introductionmentioning
confidence: 99%